Productivity augmentation of rotating wick solar still using different designs of porous breathable belt and quantum dots nanofluid - A.S. Abdullah; U. Alqsair; Mutabe S. Aljaghtham; A.E. Kabeel; Z.M. Omara; Fadl A. Essa (Ain Shams Engineering Journal, 2023)
The problem of freshwater shortage is increasing a day after day. Solar distillers are suitable devices to overcome this problem for remote areas and small families. However, these devices suffer from their low productivities. Here, two different modified designs for the distillers of rotating wick types were tested. One distiller contained a rotating wick belt with a path of “L” character shape (l-RWSS), and the other with a path of “LC” shape (LC-RWSS). In addition, the wick type was investigated for black jute and cotton wicks. Moreover, the effect of belt-rotation direction (clockwise and counterclockwise) on the still performance has been studied. The period of wick belt rotation was tested (ON = 5 min and OFF = zero, 10, 20, 30, 40, 50, and 60 min). Also, the impact of using graphene quantum dots nanofluid on the distiller performance was investigated. Experimental results obtained that the jute wick obtained more distillate than the cotton cloth. Furthermore, the productivity of LC-RWSS with counterclockwise movement of wick belt was always larger than that with clockwise direction under all different OFF times. Also, the LC-RWSS (jute wick-counterclockwise-0.1 rpm) increased the freshwater productivity by about 17 % over l-RWSS. Besides, the LC-RWSS provided higher accumulated daily productivity than l-RWSS by 19 % and 17 % with and without nanofluid, respectively. Also, the cost of freshwater obtained is 0.018 and 0.021 $/L for LC-RWSS with and without nanofluids, respectively.